1966
DOI: 10.1002/aja.1001190104
|View full text |Cite
|
Sign up to set email alerts
|

Studies on sperm survival mechanisms in the female reproductive tract of hibernating bats. I. Cytology and ultra‐structure of intra‐uterine spermatozoa in Myotis lucifugus

Abstract: Among mammals prolonged survival of spermatozoa in the reproductive tract of the female (circa 7-t months) is known in only a few species of hibernating bats, but its physiological basis remains obscure. Presumably survival involves special physiological adaptations of the spermatozoa, the uterus, or both. We have initiated studies of sperm survival mechanisms in the hibernating bat Myotis lucifugus involving analysis of the cytology and fine structure of intra-uterine sperm, the morphology and histochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…It seems unlikely, therefore, that the seminal plasma of the bat contains enough nutrient material for prolonged survival. In addition, Fawcett & Ito (1965) and Wimsatt et al ( 1966) found no evidence that bat spermatozoa contain a greater store of endo¬ genous substrates than the spermatozoa of other species. The endometrium must, therefore, supply the essential nutrients and the present work has shown it to be a highly active secretory gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems unlikely, therefore, that the seminal plasma of the bat contains enough nutrient material for prolonged survival. In addition, Fawcett & Ito (1965) and Wimsatt et al ( 1966) found no evidence that bat spermatozoa contain a greater store of endo¬ genous substrates than the spermatozoa of other species. The endometrium must, therefore, supply the essential nutrients and the present work has shown it to be a highly active secretory gland.…”
Section: Discussionmentioning
confidence: 99%
“…Austin & Bishop (1959) examined P. pipistrellus and R. ferrum-equinum and confirmed Kohlbrugge's (1913) The fine structure of the epididymal spermatozoa of M. lucifugus and E. fuscus has been described by Fawcett & Ito (1965). Wimsatt et al (1966) subsequently found only minor differences between the fine structure of uterine and epididymal spermatozoa of M. lucifugus, and suggested that uterine environmental factors were most important for sperm survival.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increased phospholipid of mitochondria1 origin may be available for sperm metabolism and may contribute to their prolonged survival (Racey, 1979). Ejaculated (intrauterine) sperm differ only in the absence of the cytoplasmic droplet and neckpiece membranous scrolls (Wimsatt et al, 1966), characteristic of the epididymal sperm of Myotis lucifugus (Fawcett and Ito, 1965).…”
mentioning
confidence: 99%
“…It (Gopalakrishna & Madhavan, 1971;Racey, Suzuki & Medway, 1975;Myers, 1977) wherein spermatozoa are stored in the uteri of nonhibernating species much the same as in hibernating Myotis lucifugus (Wimsatt, Krutzsch & Napolitano, 1966 (Tamsitt & Mejia, 1962) and A. lituratus (Tamsitt & Valdivieso, 1965) (Richardson, 1977). It is possible that this delay in ejaculation permits the spermatozoa to undergo capacitation or some other physiological preparative process essential for successful fertilization.…”
Section: Introductionmentioning
confidence: 99%